Mapping Land Use & Land Cover: A Case Study of Jhajjar District, Haryana: Exploring Land Use and Land Cover in Jhajjar District, Haryana: A Remote Sensing Approach (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Land use refers to man’s activities on earth, which are directly related to land, whereas land cover denotes the natural features and artificial constructions covering the land surface. Land use practices of a region are influenced by a number of parameters namely physical and chemical environments, socio-economic factors and needs of the masses. This study involved secondary data collection mainly from Indian remote sensing satellite- IRS LISS III satellite data.